Reincarnation in the Yoruba Ontology - Oluwaseun S. Osadola (Britain International for Academic Research (BIAR) Publisher, 2023)
Reincarnation is a religious notion that refers to the belief in some religious traditions that a component of each human being (or all living beings) continues to live after death. Numerous rebirths are associated with the concept of cleansing and refining one's inner essence, and this component is repeated in an infinite number of rebirths. However, reincarnation is not a widespread concept among the Yoruba; it occurs in just two instances: in some circumstances of untimely death, in order for an individual to fulfil his or her God-given purpose or destiny in life, and in some cases of suicide. Unlike other notions, this is not a broad term; rather, it refers to a singular occurrence that is very unpredictable. Similarly, in the second case, the concept of reincarnation is applied very loosely; it is believed that an ancestor can reincarnate in the body of a child if their gender matches that of the deceased ancestor. This study opines that this occurs only when an ancestor dies prior to the birth of a new kid; it can be a real reincarnation or a desire conveyed through the names given to a child. The departed are thought to continue to exist in the afterlife; people who remain on Earth can make contact with them, and they retain all of their hereditary characteristics. It derives it data from both primary and secondary sources.